Refugees send remittances abroad less often than other migrants - Adriana Cardozo Silva; Sabine Zinn (DIW Weekly Report, 2024)
Remittances sent by refugees to their home countries has been a hotly debated policy topic in Germany over the past years and has led to the introduction of a payment card for asylum applicants. This Weekly Report investigates how the share of people living in Germany who send remittances abroad has changed over time according to their migration background (with or without a refugee background) and which factors influence the likelihood of remitting. Based on Socio-Economic Panel (SOEP) data as well as the IAB-SOEP Migration Samples and the IAB-BAMF-SOEP Refugee Survey from 2013 to 2022, the analysis shows that migrants without a refugee background send remittances more often, while refugees are often rarely able to send remittances due to structural barriers. Thus, the political debate does not reflect reality. A person's family situation and their intention to stay in Germany long term are particularly important factors influencing the likelihood that they will send remittances abroad. In this respect, these results should contribute to a reevaluation of remittances, as they are an important instrument in achieving sustainable development goals, in stabilizing the economy in the migrants' home countries, and reducing poverty.
Keywords: F24; F22; 330; remittances; international migration